2016
DOI: 10.1007/s11837-016-2043-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Low-Voltage Tetrafluoromethane Emissions Based on the Operating Conditions of an Aluminium Electrolysis Cell

Abstract: Greenhouse gas (GHG) generation is inherent in the production of aluminium by a technology that uses carbon anodes. Most of those GHG are composed of CO 2 produced by redox reaction that occurs in the cell. However, a significant fraction of the annual GHG production is composed of perfluorocarbons (PFC) resulting from anode effects (AE). Multiple investigations have shown that tetrafluoromethane (CF 4 ) can be generated under low-voltage conditions in the electrolysis cells, without global anode effect. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Previous research by the current authors [18] demonstrated that the standard deviation among individual anode currents is the strongest indicator of LVAE. Therefore, it is easily possible to calculate the standard deviation of the individual anodic currents resulting from the simulator to predict the risk of LVAE.…”
Section: Risk Of Low-voltage Anode Effects (Module 7)mentioning
confidence: 62%
See 3 more Smart Citations
“…Previous research by the current authors [18] demonstrated that the standard deviation among individual anode currents is the strongest indicator of LVAE. Therefore, it is easily possible to calculate the standard deviation of the individual anodic currents resulting from the simulator to predict the risk of LVAE.…”
Section: Risk Of Low-voltage Anode Effects (Module 7)mentioning
confidence: 62%
“…However, as the alumina concentration is rarely measured during normal operation of an electrolysis cell, such a model can hardly be used to quantify PFC emissions resulting from LVAE. To counter this problem, the authors of this article previously developed a complex multivariate model [18] that uses seven, monitored cell indicators to account for the level of PFC emitted during LVAE. The results of this analysis demonstrated that the dominant cell indicator that can reveal information on the presence of LVAE in the electrolysis cell is the standard deviation among all individual anode currents.…”
Section: ½6mentioning
confidence: 99%
See 2 more Smart Citations
“…But when an AE occurs, it reduces the cleaning efficiency and lowers the quality of aluminium products. In addition, AE is also accompanied by a high cell temperature, extensive material waste, high energy consumption, and harmful fluoride gas emission [4]. Thus, the frequency with which AE occurs must be controlled to an acceptable level.…”
mentioning
confidence: 99%